2010
DOI: 10.28945/1195
|View full text |Cite
|
Sign up to set email alerts
|

Web Design and Company Image

Abstract: Research reported in this paper looks at the interrelationship between web site design and company image. The research has found that visiting and evaluating company's web sites can change customers' perceptions about the image of that company. The paper also shows the influence of specific website attributes in portraying the image of the companies. Some web site features such as navigability, content, and first impressions, influence a company's image more than others. Additionally, the research shows gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Another variable taken into account in this study is the variable of confidence in website. The design and content of the websites are one of the issues that have a significant impact on the company image and the potential of the enterprise (Kuzic et al 2010). In our study, it was determined that confidence in website positively affected both perceived value and customer satisfaction.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Another variable taken into account in this study is the variable of confidence in website. The design and content of the websites are one of the issues that have a significant impact on the company image and the potential of the enterprise (Kuzic et al 2010). In our study, it was determined that confidence in website positively affected both perceived value and customer satisfaction.…”
Section: Discussionmentioning
confidence: 79%
“…In addition that the content of a website is a very important issue for e-commerce sites, information, navigation and visual design of an effective website should be quite satisfactory (Cyr ve Bannon, 2005). On the other hand, the researches in the related literature found that e-service quality had an impact on purchasing trend of customers, customer satisfaction (Song et al 2012;Gures et al 2015;Ting et al 2016), brand and company image of the website (Kuzic and Giannatos, 2010), behaviour of e-loyalty and positive consumer tendencies (Kim and Niehm, 2009;Udo et al 2010).…”
Section: E-service Qualitymentioning
confidence: 99%
“…(1) "Judged appeal": do users report that a feature is desirable or its presence attracts them to shop one site rather than another? (notably, Belanger et al, 2002;Blake and Neuendorf, 2004;Blake et al, 2005Blake et al, , 2009Blake et al, , 2010Guo and Salvendy, 2009;Hwang et al, 2006;Kuzic et al, 2010;Liao et al, 2009;Mukhopadhyay et al, 2008;Papatla, 2011;Post et al, 2002;Szymanski and Hise, 2000;von Dran, 2001/2002;Zhang et al, 2001).…”
Section: Bases Of Importancementioning
confidence: 99%
“…Institutions today, employ rich web-based contents as means for high visibility, which will ultimately aid them to capitalize on profits and benefit by promoting their products in a competitive market. A good website can change, recreate and refocus a user's image of an organization (Kuzic et al, 2010). Designing such website is quite a daunting task that is rippled with many challenging feats such as navigation, contents, openness etcall of which guides the users as they peruse a site's pages, to keep users' interest engaged and lead to satisfied users' experience, and knowledge as outcome its byproduct cum outcome (Weiderman &Mgidana, 2004).…”
Section: Introductionmentioning
confidence: 99%